The application of artificial intelligence in audits: evidence from audit firms in Malaysia - Nik Abdul Majid, Wan Zurina; Asat, Siti Haliza; Tumiran @ Kamal Nasser, Siti Dalina; Idris, Nor Asiah; Muhammad, Kamaruzzaman; Abdulatif, Kamaruzaman (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2025)
This research sought to provide answers to what challenges audit firms face in the application of artificial intelligence (AI) in audit work and how AI transforms audit performance. The study adopted a qualitative analysis of reviewing the literature in relation to audit challenges and audit transformation with AI and by interviewing auditors from the Big 4 firms in Malaysia. The data was analysed manually and also using Nvivo 14.0. The study found that IT infrastructure and the operational software transition were considered as the main challenges in applying AI in audit firms in Malaysia. In addition the application of AI supported big data processing, changed the way of auditing and mitigated the audit risks and thus improved audit quality. The study provides further insights on the application of AI in audit firms in Malaysia. The findings may also increase the confidence of other Malaysian audit firms in investing in artificial intelligence-based auditing systems. The findings of the study add to the literature on AI by enabling researchers and practitioners to understand the application of AI in audit work and to find solutions to any obstacles. The originality of this research is asserted by the novelty of the study and limited source of information on AI and auditing in Malaysia setting.